The Potential of Local Food Diversification in Supporting Sustainable Food Security in Maluku Islands - Johan Riry; Marlita Herlin Makaruku; Vilma Laurien Tanasale (Research Synergy Foundation, 2023)
Every region in Indonesia has food potential according to the region's characteristics, as is the case with Maluku, an archipelago province with a diverse group of small islands. Due to the distinctive characteristics of each island, sufficient knowledge regarding the condition of potential food and its constraints is needed to avoid food shortages. The study aimed to analyze the constraints and potential of local food diversification on each island situated in the XII Island Clusters of Maluku to achieve the fulfillment of sustainable food and food security for each of these islands. The data used was descriptive data collected from a significant number of previous research journals, documents, and field notes. Data analysis was conducted using a qualitative descriptive method that attempts to describe and interpret food diversification potentials and constraints in XII GP in Maluku based on the reality through a thorough literature study. The analysis results showed that in most of the small islands in Maluku, the land was dry and hilly, the rainfall was low, the tilling layer was thin, the soil fertility was low, and it was easily degraded. The resources of farmers with qualified agricultural knowledge were still very limited. However, the potential gained was that there were six main types of food spread across XII GP, namely sago, corn, barley (hotong), upland rice, sweet potatoes, and bananas, which can be obtained and processed to fulfill the food needs of the community and ultimately achieve sustainable food security for everyone in the islands.